Phenotypic Features and Salivary Parameters in Patients with Ectodermal Dysplasia: Report of Three Cases - Mônica Fernandes Gomes; Luigi Giovanni Bernardo Sichi; Lilian Chrystiane Giannasi; José Benedito Oliveira Amorim; João Carlos da Rocha; Cristiane Yumi Koga-Ito; Miguel Angel Castillo Salgado (Hindawi Limited, 2018)
Ectodermal dysplasia (ED) is a rare hereditary disorder affecting the development of ectoderm-derived organs and tissues. The aim of this study was to describe phenotypic features and the therapeutic approach in dentistry among three patients with ED, correlating their data with the literature. Additionally, to investigate the salivary gland disorders and their impacts on oral microbiota, we performed salivary tests, including salivary flow rate, salivary buffering capacity, and concentration levels of mutans streptococci, lactobacilli, and yeasts. All patients presented oligodontia, resulting in a significant masticatory dysfunction and aesthetic impairment. The counts of mutans streptococci n=3 and yeasts n=2 were high; on the other hand, the count of lactobacilli n=3 was low. Therefore, salivary and microbiological tests showed that the patients with ED, particularly the hypohidrotic type, presented a high risk of enamel caries and susceptibility to oral infections, which may be likely triggered by reduction of salivary flow and/or possible immunological disorders.